Automatic Mesh Adaptation for Magnetic Pulse Forming Simulations - Garcia, J. O.; Alves Z., J. R.; Ripert, U.; Barlier, J.; Bay, F. (Technische Universität Dortmund, 2025)
Multiphysics coupling simulation for the electromagnetic modelling of pulse forming technology comes with several challenges: Large deformations with high strain rates, fast impact conditions, multiple phenomena with distinctive proper time scales, complex geometries, etc. In order to accurately represent the electromagnetic phenomena together with the thermomechanical effects in a reliable manner a key step is the ability to measure the numerical error intrinsic to the discretization scheme (typically within the finite element framework) and use of automatic mesh adaptation techniques. In this work, an a posteriori error estimator-based technique adapted to the electromagnetic phenomena is presented together with an anisotropic automatic mesh adaptation technique. These methods are rooted in the understanding of the underlying physical phenomena, bringing as consequence: ease of the modelling stage as numerical results are less dependent on initial mesh settings. Accelerated simulation times as computation resources are adapted automatically to increase accuracy where needed and decrease mesh density otherwise. All of this in a natively distributed-memory parallel framework which can be scaled for large problems within the simulation software FORGE.
Keywords: Metal Forming; Finite element method (FEM); 620; 670; Magnetumformen; Simulation; Finite-Elemente-Methode